Anthropomorphic and Factual Approaches in Komodo Dragon Conservation Awareness Program for Elementary School Students: Initial Study - Kamil, Puspita Insan; Susianto, Harry; Purwandana, Deni; Ariefiandy, Achmad (Applied Environmental Education and Communication, 2020)
Increasing wildlife awareness is a commonly used approach in community conservations programs. However, in Indonesia, this approach has rarely been quantitatively evaluated for its effectiveness. In North Flores, we carried out a short Komodo dragon ("Varanus komodoensis") conservation awareness program for elementary school students. The program used a mixed communication approach combining an anthropomorphic storybook and factual information about Komodo behavior delivered through a presentation and a video. The results from this initial study showed that the program had improved students' knowledge of Komodo dragon biology and conservation efforts.
Publisher: Routledge
Keywords: Animals; Communication Strategies; Conservation (Environment); Elementary School Students; Foreign Countries; Knowledge Level; Personality Traits; Video Technology